KEPEMIMPINAN DAN MANAJEMEN KEPALA MADRASAH (Studi Kasus Kepala MTsN Sungayang Berprestasi Tingkat Nasional) - Sastra Deni R (IAIN Batusangkar, 2018)
This research is aimed at describing the leadership of the Head Master of MTsN Sungayang in achieving a better quality school. The research applied a qualitative paradigm. The techniques of data collection of this study were interviews, observation and documentary study. The technique of data analysis applied the interactive model by Miles and Huberman. For checking data trustwohiness, triangulation technique was applie, namely by comparing the results of observation data with those of interview, and documentation. The findings of the study show that the school principal plans the programs, performing short speeches (muhadaroh) in the Madrasah, providing religious vocabulary, habituating the students to perform Dhuha prayer and noon prayer together, evaluating classrooms cleanliness, making Madrasah wall magazine, creating Madrasah Health Unit (UKS), performing activities of Sports and Arts, of social like takziyah, visiting the sick people, and collecting money for social funds.